2023
DOI: 10.1021/acsomega.2c07591
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanoparticles Modified by Carbon Quantum Dots for the Photocatalytic Removal of Synthetic Pigment Pollutants

Abstract: Synthetic pigment pollutants caused by the rapid development of the modern food industry have become a serious threat to people's health and quality of life. Environmentally friendly ZnO-based photocatalytic degradation exhibits satisfactory efficiency, but some shortcomings of large band gap and rapid charge recombination reduce the removal of synthetic pigment pollutants. Here, carbon quantum dots (CQDs) with unique up-conversion luminescence were applied to decorate ZnO nanoparticles to effectively construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…For instance, Zhang et al have grown ZnO nanowires on the glass substrate using the hydrothermal method, and the average lifetime exhibited by ZnO nanowires is 13.9 ns. Xu et al reported the synthesized ZnO nanoparticles with an average size of 80 nm, exhibiting an average lifetime of 5.642 ns . In a study by Sunandan and coworkers, ZnO nanoparticles were prepared by the hydrolysis and microwave methods, where the ZnO nanoparticles prepared by hydrolysis method exhibited an average lifetime of 26.8 ns and particles prepared by the conventional method exhibited 25.2 ns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Zhang et al have grown ZnO nanowires on the glass substrate using the hydrothermal method, and the average lifetime exhibited by ZnO nanowires is 13.9 ns. Xu et al reported the synthesized ZnO nanoparticles with an average size of 80 nm, exhibiting an average lifetime of 5.642 ns . In a study by Sunandan and coworkers, ZnO nanoparticles were prepared by the hydrolysis and microwave methods, where the ZnO nanoparticles prepared by hydrolysis method exhibited an average lifetime of 26.8 ns and particles prepared by the conventional method exhibited 25.2 ns.…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al reported the synthesized ZnO nanoparticles with an average size of 80 nm, exhibiting an average lifetime of 5.642 ns. 49 In a study by Sunandan and coworkers, 50 ZnO nanoparticles were prepared by the hydrolysis and microwave methods, where the ZnO nanoparticles prepared by hydrolysis method exhibited an average lifetime of 26.8 ns and particles prepared by the conventional method exhibited 25.2 ns. Sonmez et al have prepared a ZnO thin film using a spray pyrolysis technique, 47 which exhibited nanorod morphology, and the fluorescence lifetime of ZnO nanorods was estimated to be 1.56 ± 0.05 ns.…”
Section: Time-resolved Fluorescence Studiesmentioning
confidence: 99%
“…Thus, the band gap modification of ZnO through silver doping extends the absorption of light at the visible wavelength. The high intensity and broad absorption peak of Ag/ZnO through the entire solar spectrum can also facilitate enhanced light absorption capacity both in the UV and visible regions for photocatalytic activities [ 40 ]. The band gap energy of Ag/ZnO is lower than that of ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…The use of Zinc oxide (ZnO) has garnered considerable interest due to its high photoluminescence in visible regions, low cost, and biocompatibility [16][17][18][19][20]. The use of ZnO nanoparticles as photocatalysts [21][22][23][24][25][26], anti-bacterial agents [27], sensor components [28,29], drug delivery agents [30], and others have been reported in recent studies.…”
Section: Introductionmentioning
confidence: 99%